2020
DOI: 10.3389/fbioe.2020.00592
|View full text |Cite|
|
Sign up to set email alerts
|

Immune and Clinical Features of CD96 Expression in Glioma by in silico Analysis

Abstract: Background Immune checkpoints target regulatory pathways in T cells that enhance antitumor immune responses and elicit durable clinical responses. As a novel immune checkpoint, CD96 is an attractive key target for cancer immunotherapy. However, there has been no integrative investigation of CD96 in glioma. Our study explored the relationship between CD96 expression and clinical prognosis in glioma. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…Zhang et al showed that high expression of CD96 was present in the malignant molecule phenotype, including IDH wild type and mesenchymal subtype. They also stressed that it had a positive association with inflammatory activities (89). Indeed, C D 9 6 s h o w e d a h i g h c o n c o r d a n c e w i t h i m m u n e checkpoints such as PD-1, CTLA-4, TIGIT, TIM-3, NR2F6, and GITR, which would suggest a potential synergism (89).…”
Section: Tigit/cd96mentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al showed that high expression of CD96 was present in the malignant molecule phenotype, including IDH wild type and mesenchymal subtype. They also stressed that it had a positive association with inflammatory activities (89). Indeed, C D 9 6 s h o w e d a h i g h c o n c o r d a n c e w i t h i m m u n e checkpoints such as PD-1, CTLA-4, TIGIT, TIM-3, NR2F6, and GITR, which would suggest a potential synergism (89).…”
Section: Tigit/cd96mentioning
confidence: 99%
“…They also stressed that it had a positive association with inflammatory activities (89). Indeed, C D 9 6 s h o w e d a h i g h c o n c o r d a n c e w i t h i m m u n e checkpoints such as PD-1, CTLA-4, TIGIT, TIM-3, NR2F6, and GITR, which would suggest a potential synergism (89). In addition to that, they discovered that higher CD96 expression predicted worse survival rates in glioma and GBM patients overall.…”
Section: Tigit/cd96mentioning
confidence: 99%
“…The mesenchymal subtype is characterized by higher percentages of cycling cells and neo-angiogenesis, with a highly invasive nature and poor prognosis (16). Furthermore, biological function analysis revealed that immune checkpoint receptor target was highly enriched in mesenchymal subtype glioma and might be a potential marker of mesenchymal subtype (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, WHO grade was closely associated with OS. 12 The work flow diagram of this study was depicted in Figure S1 .…”
Section: Methodsmentioning
confidence: 99%